The difference between energy consumption and energy cost: Modelling energy tariff structures for water resource recovery facilities. (15th September 2015) - Aymerich, I.; Rieger, L.; Sobhani, R.; Rosso, D.; Corominas, Ll.
Abstract: The objective of this paper is to demonstrate the importance of incorporating more realistic energy cost models (based on current energy tariff structures) into existing water resource recovery facilities (WRRFs) process models when evaluating technologies and cost-saving control strategies. In this paper, we first introduce a systematic framework to model energy usage at WRRFs and a generalized structure to describe energy tariffs including the most common billing terms. Secondly, this paper introduces a detailed energy cost model based on a Spanish energy tariff structure coupled with a WRRF process model to evaluate several control strategies and provide insights into the selection of the contracted power structure. The results for a 1-year evaluation on a 115, 000 population-equivalent WRRF showed monthly cost differences ranging from 7 to 30% when comparing the detailed energy cost model to an average energy price. The evaluation of different aeration control strategies also showed that using average energy prices and neglecting energy tariff structures may lead to biased conclusions when selecting operating strategies or comparing technologies or equipment. The proposed framework demonstrated that for cost minimization, control strategies should be paired with a specific optimal contracted power. Hence, the design of operational and control strategies must take into account the local energy tariff. Highlights: A framework to model energy tariff structures was proposed. 7–30% difference was obtained when comparing TOU structure vs average energy price. The framework was applied to compare aeration control strategies. Proper selection of contracted power resulted in savings without investment.